2017
DOI: 10.21873/anticanres.11873
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Nab-Paclitaxel as Second-line Chemotherapy for Locally Advanced and Metastatic Non-small Cell Lung Cancer

Abstract: Nab-paclitaxel is an effective chemotherapy for locally advanced and metastatic NSCLC as treatment and has a superior application prospect for squamous NSCLC. Toxicity is generally mild and manageable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
1
6
1
Order By: Relevance
“…Lung cancer is the highest mortality of all types of cancer worldwide, causing 27% of cancer deaths [ 1 ]. Taxane-based chemotherapies are used to treat approximately 70% of lung cancer patients [ 2 , 3 ]. Unfortunately, 40% of these patients recur or relapse after initial treatment as a result of acquired resistance [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the highest mortality of all types of cancer worldwide, causing 27% of cancer deaths [ 1 ]. Taxane-based chemotherapies are used to treat approximately 70% of lung cancer patients [ 2 , 3 ]. Unfortunately, 40% of these patients recur or relapse after initial treatment as a result of acquired resistance [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the ORR and DCR were 26.5% and 82.4%, respectively; the median PFS and OS were 6.0 and 11.0 months, respectively. Previous studies of nab-PTX alone in second or further line treatment of NSCLC reported a PFS of 3.5-6.6 months and an OS of 6.8-15.7 months, with ORRs ranging from 16.1%-35.5% 27 , 28 , 37 - 40 . A study of nab-PTX combined with carboplatin reported a PFS of 4.0 months and an OS of 14.0 months 41 .…”
Section: Discussionmentioning
confidence: 97%
“…This is also consistent with the known safety profiles of nab-PTX and bevacizumab 21 - 23 , 30 . Using nab-PTX alone, the rates of grade 3-4 leukopenia, neutropenia, and anemia have been reported to be 5%-49%, 2%-69%, and 0%-32% 24 , 27 , 28 , 37 - 40 . In a study of nab-PTX combined with carboplatin, neutropenia, thrombocytopenia, and anemia were observed in 28.0%, 12.0%, and 8.0% of the patients, respectively 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That result was inspiring since the basic treatment options for SCC at the time were limited[9]. Several studies have also demonstrated the efficacy and tolerability of nab-PC as second-line or late-phase chemotherapy in advanced SCC[10-14]. For our patient, nab-PC plus cisplatin was first administered as the second-line therapy, due to the patient’s poor response to the DP therapy; it showed consid-erable efficacy and led to a total PFS of 23.9-mo, without obvious adverse effects.…”
Section: Discussionmentioning
confidence: 99%